Effect of Cu alloying on S poisoning of Ni surface via ab initio thermodynamics calculations - Kim, Ji-Su; Kim, Byung-Kook; Kim, Yeong-Cheol (WILEY-V C H VERLAG GMBH, 2014)
We investigated the effect of Cu alloying on S poisoning of a Ni surface via ab initio thermodynamics calculations. We found that the Cu segregation on the Ni surface weakened the S adsorption on the surface. In order to understand the weakening of the S adsorption, the S adsorption energy was evaluated as a function of d-band center with consideration of the weighted d-band scheme. The increase of Cu concentration on the top surface shifted the d-band center downward from the Fermi-level, and therefore decreased the S adsorption energy. The Cu segregation on the top surface played a key role for the improvement of S tolerance of the NiCu alloy surface. (C) 2014 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim
Keywords: DENSITY-FUNCTIONAL THEORY; TOTAL-ENERGY CALCULATIONS; GAS SHIFT REACTION; HYDROGEN-PRODUCTION; SULFUR TOLERANCE; ANODE MATERIALS; SOFC ANODE; SEGREGATION; ADSORPTION; COPPER